2013
DOI: 10.4103/0253-7176.119502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Patients with Type II Diabetes Mellitus and its Impact on Quality of Life

Abstract: Background:Diabetes mellitus (DM) is a frequently encountered chronic metabolic disease with various complications throughout its course, which causes severe restriction and disability in an individual's life. It has been well documented that the incidence of depression is higher in diabetic patients and co-morbid depression causes further deterioration in the quality of life in diabetic patients.Aims:To study the prevalence of depression and its impact on quality of life in patients with type II DM.Settings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 18 publications
4
25
1
2
Order By: Relevance
“…The mean score of practical social support was low in comparison with other areas [24]. These results are consistent with the results of other studies which showed that the highest social support was the verbal type and include a discussion on the benefits of sport and verbal encouragement.…”
Section: Discussionsupporting
confidence: 90%
“…The mean score of practical social support was low in comparison with other areas [24]. These results are consistent with the results of other studies which showed that the highest social support was the verbal type and include a discussion on the benefits of sport and verbal encouragement.…”
Section: Discussionsupporting
confidence: 90%
“…The combination of diabetes and depression is associated with decrease in functional abilities and self-care. 1 - 4 Rustad et al 5 conducted a meta-analysis of 42 published studies that included 21,351 adults, and found that the prevalence of major depression in people with diabetes was 11%, and the prevalence of clinically relevant depression was 31%. Diabetes mellitus is a common health problem with extreme medical and economic consequences.…”
mentioning
confidence: 99%
“…However, this finding could not be explained fully because the situation of the female patient was worse which showed the evidence for gender inequalities. 28 Another study 29 found the deterioration of the QoL of patients with type 2 DM by the presence of depression. This finding resulted on the conclusion that the QoL of the subject could be made better by treating depression.…”
Section: Regular 0ªmentioning
confidence: 99%